Policies to reduce pollution and maintain economic sustainability with the use of renewable energy in European Union countries - Ali, Walid; Raissi, Nizar (Center of Biomass & Renewable Energy (CBIORE), 2024)
A major global challenge humanity faces today is how to strike a balance between the mitigation of environmental degradation and the achievement of sustainable economic growth. In this respect, this study applied an autoregressive distributed lag to the panel data of 28 European Union (EU-28) countries from 2000 to 2020. The study’s results confirm the existence of a positive and significant long-term nexus between environmental sustainability, renewable energy consumption, and economic growth in EU-28 countries. Furthermore, the empirical results indicate that real capital formation, carbon emissions, and other environmental factors are the principal determinants of long-term growth in the EU. Using Dumitrescu and Hurlin’s (2012) research, we found that the non-causality in the heterogeneous panel results showed long-run bidirectional causal relationships among renewable energy consumption, economic growth, and other growth determinants. Therefore, we can say that the consumption of renewable energy sources in the 28 EU countries is a reliable way to mitigate environmental pollution. This indicates that attaining the Sustainable Development Goals by using renewable energy and reducing carbon emission is feasible in EU-28 countries by 2030 and should also be adopted by all countries as an effective global policy.